IDENTIFIKASI KESESUAIAN LOKASI TEMPAT PEMAKAMAN UMUM DI KECAMATAN SINGKAWANG BARAT - Ratna Juwita, Dewi; Wulandari, Agustiah; Zulkifli Mulky, Gusti; Sophia Lubis, Mira (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
The distribution of locations for public cemeteries in West Singkawang Sub-District largely ignores the location suitability provisions based on Government Regulation Number 9 of 1987. One of them is the Al-Firdaus Islamic TPU in Tengah Kelurahan because it is close to settlements. The purpose of this study was to identify the suitability of the location of the distribution of public cemeteries in West Singkawang District and provide recommendations for locations for the provision of new public cemeteries. This study used a quantitative approach with overlay and scoring analysis techniques. The results of this study were obtained from six public cemeteries, only one of which had a "fairly appropriate" classification, namely Baitul Huda Islamic Public Cemetery and five other public cemeteries had a "less appropriate" classification. The recommendations for new locations for the provision of public cemeteries are outside Singkawang Barat District, namely in Central Singkawang District, North Singkawang District, and South Singkawang District.